Analisis Tingkat Kecukupan Modal Dan Loan to Deposit Ratio Terhadap Profitabilitas - Hiras Pasaribu; Rosa Luxita Sari (Jurnal Telaah dan Riset Akuntansi, 2015)
The study purposes to determine the magnitude of the effect level of Capital Adequancy (Capital Adequancy Ratio - CAR) and liquidity (Loan to Deposit Ratio - LDR) simultaneously and partially on bank profitability. The research are the banks that being ranked according to ICMD 2009. The data used is the ratio of CAR, LDR, and profitability (ROA) in 2004 to 2008. Data were analyzed with multiple regression analysis. Research shows simultaneously and partial capital adequacy ratio (CAR) and the level of Loan to Deposit Ratio (LDR) have a significant effect on profitability (ROA).KEYWORDS : CAR, LDR, and profitability (ROA)